Respiratory allergies and house dust mites: evaluating public awareness in Riyadh, Saudi Arabia – a cross-sectional study - Al-Shouli, Samia T.; Kurdee, Zeyad; Meo, Sultan Ayoub; Alhabardi, Samiah; Alnasser, Abdulaziz; Almogbel, Bader; Abdulaziz, Khalid; Alquwayi, Naif; Alhanaya, Saad; Alshehri, Sultan; Hussein, Yazeed; Hussein, Mohammed (Frontiers in Medicine, 2025)
ObjectivesRespiratory allergies are a highly challenging and growing public health problem. The house dust mites (HDM) are common allergens that trigger respiratory allergic reactions. This study aimed to investigate the knowledge and attitudes of the general population in Riyadh, Saudi Arabia, regarding HDM-induced respiratory allergy.MethodsThis cross-sectional study recruited a total of 917 subjects, 481 males (52.5%) and 436 females (47.5%). An online questionnaire was developed and underwent a pilot process to assess its clarity, relevance, and comprehensiveness. The questionnaire had 19 questions divided into three parts (sociodemographic, knowledge, and attitudes). The questionnaire was distributed via social media platforms, including email and WhatsApp.ResultsThe most common reported allergies were sinusitis (17.1%), asthma (12.4%), rhinitis (11.6%), eczema (6.2%), urticaria (2.5%), rash (1.5%), and conjunctivitis (1.3%). Male participants (mean = 5.11, SD = 2.14) had a significantly lower mean knowledge score than females (mean = 6.03, SD = 1.76), p = 0.001. The participants aged 46–59 (mean = 6.05, SD = 1.81) had the highest knowledge (p = 0.001), participants with a postgraduate degree (mean = 6.04, SD = 1.86) had the highest knowledge, followed by those with a bachelor’s degree or diploma, high school graduates, and those with less than a high school education (p = 0.006). A sizable portion, 47.7% (437) of respondents, correlated HDM-induced respiratory allergies with living environments characterized by poor hygiene and crowded residential places.ConclusionThe most commonly reported allergies were sinusitis, asthma, rhinitis, eczema, urticaria, rash, and conjunctivitis. The majority of participants had limited knowledge of HDM-induced allergy; male participants demonstrated significantly lower knowledge compared to females. Participants aged 46–59 years who held a postgraduate degree showed the highest level of knowledge. A sizable portion of the participants correlated HDM-induced respiratory allergies with living environments characterized by poor hygiene and crowded residential places.